2021
DOI: 10.1177/17562864211021182
|View full text |Cite
|
Sign up to set email alerts
|

Acute reperfusion therapies for acute ischemic stroke patients with unknown time of symptom onset or in extended time windows: an individualized approach

Abstract: Recent randomized controlled clinical trials (RCTs) have revolutionized acute ischemic stroke care by extending the use of intravenous thrombolysis and endovascular reperfusion therapies in time windows that have been originally considered futile or even unsafe. Both systemic and endovascular reperfusion therapies have been shown to improve outcome in patients with wake-up strokes or symptom onset beyond 4.5 h for intravenous thrombolysis and beyond 6 h for endovascular treatment; however, they require advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 186 publications
(323 reference statements)
0
6
0
Order By: Relevance
“…Previously, EVT for acute ischemic stroke with LVO was recommended within specific time windows, especially in those within the 6 h from stroke onset. Though the potentially salvageable tissue is affected by the severity and duration of ischemia, the speed of "tissue clock" may differ in individuals [19]. Recent trials have shown the benefits of EVT compared to the best medical treatment during the extended time of 6-24 h in image-based selected patients [1].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, EVT for acute ischemic stroke with LVO was recommended within specific time windows, especially in those within the 6 h from stroke onset. Though the potentially salvageable tissue is affected by the severity and duration of ischemia, the speed of "tissue clock" may differ in individuals [19]. Recent trials have shown the benefits of EVT compared to the best medical treatment during the extended time of 6-24 h in image-based selected patients [1].…”
Section: Discussionmentioning
confidence: 99%
“…Recombinant tissue plasminogen activator was given intravenously within 4.5 h after symptom onset in indicated patients [9]. Patients underwent endovascular treatment in accordance with the national clinical practice guideline and local protocol [10]. The individual stroke risk and the bleeding risk in patients with AF were calculated using the CHA2DS 2-VAS c -score and the HAS-BLED score, respectively.…”
Section: Participants and Clinical Datamentioning
confidence: 99%
“…There were no significant differences in terms of demographics and vascular risk factors between the two groups. Compared with those without RVR, patients with RVR had higher initial NIHSS scores (10 [5-16] vs. 7 [2][3][4][5][6][7][8][9][10][11][12][13][14]; p = 0.001), higher prevalence of persistent AF (95.3 vs. 61.5%; p < 0.001), lower EF (56 ± 11 vs. 59 ± 8%; p = 0.006), and a higher proportion of patients with a poor outcome at 3 months (mRS 3-6; 54.7 vs. 38.0%; p = 0.004). Prior history of taking angiotensin receptor blocker/angiotensin-converting enzyme inhibitor (24.4 vs. 36.5%; p = 0.030) and antiarrhythmic drugs (0 vs. 6.0%; p = 0.020) were lower in those with RVR than without.…”
Section: Comparison Between Patients With and Without Rvrmentioning
confidence: 99%
“…A large proportion of the included patients (138 out of 316) finally received CTP, and among them the vast majority (91%) had a penumbral pattern. 82 The low percentage of patients with absence of target mismatch (9%) could be explained by the fact that poor collaterals, which were an exclusion criterion in the ESCAPE trial, are most likely associated with non-penumbral patterns. This observation implies the significant overlap between CTP perfusion values and the different collateral grades (good, moderate, and poor tissue 'perfusion') as assessed with the qualitative method of ESCAPE trial.…”
Section: Mt In the 0-6 Hours Windowmentioning
confidence: 99%